The Effect of Cultural Values on Enterprise Performance through Entrepreneurial Orientation - Yustin Sesa; Jusni Ambo Upe; Fauziah Umar (Magister Management, Hasanuddin University, 2021)
Nowadays, efforts to develop the welfare of rural communities in Indonesia are driven by village-owned enterprises which are being developed by villages. The study examines linking the effect of cultural values on employee performance with entrepreneurial orientation as an intervening in the case of village-owned enterprises in North Toraja Utara, South Sulawesi Province. The study collected data from 84 village-owned enterprises with the use of a five-Likert scale. To analyze the research model, the study applied path analysis. Statistical findings showed that cultural value and entrepreneurial orientation have a positive and significant effect on employee performance. It is also found that entrepreneurial orientation can mediate the relationship between cultural values and employee performance.